Evaluation of B-Lactam Resistance among Phylogenetic Groups of Diarrheagenic Escherichia Coli - Nawras Najah Mubark; Heyam Emad Al. Qurabiy; Nedhal Hameed Sajet (Journal of Science in Medicine and Life, 2025)
Background: Diarrheagenic Escherichia coli (DEC) is one of the common causes of diarrhea in all ages and its treatment is necessary with appropriate antibiotics, so the current study aims to isolate and diagnose DEC according to the phylogenotype to know which group is the causative agent of diarrhea and know its resistance to the most common antibiotics represented by beta-lactams. Methods: The current research included 150 stool samples from individuals with diarrhea, and after diagnosing bacteria by culture media and biochemical tests, it was found that only 118 samples had DEC as the causative pathogen of diarrhea. Antibiotic sensitivity test for all DEC isolates preform by 10 commonly used antibiotics belonging to the beta-lactam. After DNA extraction, the genotypes were determined using multiplex PCR technique. Results: According to multiplex PCR-based phylogenetic analysis, group B2 represent the majority of the collected DEC isolates (70.3%) followed by D (17%) and group B1 (8.5%) but group A appeared in 5 samples only. Moreover, all phylogenetic groups (100%) and subgroups (100%) were resist to penicillin and amoxicillin. Group D and their subgroups showed complete resistance (100%) to Penicillin, Ampicillin, Cefalexin, Cefepime and Amoxicillin, at the same time they showed high resistance to the Cefotaxim, while they were more sensitive to Ceftriaxone. groups A and B1 showed complete resistance (100%) to both penicillin and amoxicillin also they have high resistance to Cefalexin (80% and 90% respectively) and Cefotaxim (80% for each group), while they were 100% sensitive to ceftriaxone. In addition, group A have 100% sensitivity to Ampicillin. Subgroup D2 isolates were the most resistant among the subgroups, as they were 100% resistant to other antibiotics such as Ampicillin, Cefalexin, Cefixime and Cefepime. Subgroup A0 showed a high sensitivity (100%) to Ampicillin, Cefixime, Ceftriaxone, Imipenem, Meropenem and Cefepime. In conclusion: Group B2 and their subgroups were the main cause of diarrhea and they showed high resistance to most antibiotics, while the effective treatment for it was Ceftriaxone and Meropenem.